A LITERATURE STUDY OF BENEFITING K-BEARING SILICATE ROCKS AS RAW MATERIALS FOR POTASSIUM FERTILIZER - Agus Wahyudi; Tatang Wahyudi (Indonesian Mining Journal, 2013)
As an agricultural country Indonesia requires NPK fertilizer up to 2.6 million tons per year. However, such a number is mostly fulfilled by imports, particularly potassium (K) fertilizer. Almost a 100% of K-fertilizer comes from Canada and Russia in the form of KCl (sylvite) salt. Indonesia does not have sylvite mineral, but retains some K-bearing minerals such as K-feldspar and leucite. Both are different in characteristics from sylvite. K-feldspar and leucite are the alumino-silicate minerals. They require special treatment to process them into K-fertilizer. Several techniques can be applied to process both minerals, such as by mechano-chemistry, leaching, alkali fusion and bioleaching. Research on the utilization of K-source minerals as a raw material for K fertilizer is rela- tively rare. The opportunity to conduct such a research is widely open, as currently conducted by the Research and Development Centre for Mineral and Coal Technology.